Protein-induced low molecular weight hydrogelator self-assembly through a self-sustaining process. Issue 18 (20th March 2019) - Rodon Fores, Jennifer; Criado-Gonzalez, Miryam; Schmutz, Marc; Blanck, Christian; Schaaf, Pierre; Boulmedais, Fouzia; Jierry, Loïc
Abstract : Electrostatic interaction between a protein and suitable peptides allows the continuous formation of hydrogelators which self-assemble from the protein. Abstract : Controlling how, when and where a self-assembly process occurs is essential for the design of the next generation of smart materials. Along this route, enzyme-assisted self-assembly is a powerful tool developed during the last decade. Here we introduce another strategy allowing for spatiotemporal control over peptide self-assemblies. We use a Fmoc-peptide precursor in dynamic equilibrium with its low molecular weight hydrogelator (LMWH) through a reversible disulfide bond. In the absence of proteins, no self-assembly of the hydrogelator is observed. In the presence of proteins, their interactions with the precursor initiate a self-assembly process of the hydrogelator around them. This self-assembly displaces the equilibrium between precursor and LMWH according to Le Chatelier's principle, producing new hydrogelators available to pursue the self-assembly growth. One thus establishes a self-sustaining cycle fuelled by the self-assembly itself until full consumption of the LMWH. For proteins in solutions this process can lead to a supramolecular hydrogel whereas for proteins deposited on a surface, the gel growth is initiated exclusively from the surface.